2017
DOI: 10.1007/978-3-319-56397-8_58
|View full text |Cite
|
Sign up to set email alerts
|

Strain Localization as a Function of Topological Changes in Mesoscopic Granular Structures

Abstract: In this paper, the microphysical aspects leading to the occurrence of a localized failure were investigated by examining the initial emergence of ubiquitous potential slip planes and their link to the shear band development. A Discrete Element Model (DEM) representing a dense granular assembly was considered and subjected to a biaxial compression such that it undergoes localized failure into a persistent shear band. The paper includes both energetic and meso-structural analyses based on so-called minimal close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…(2005) due to a lack of spatial and temporal resolution in their particle imaging velocimetry (PIV) analysis. Along these lines, in biaxial compression experiments, a number of authors have reported that pre‐peak deformation takes the form of distinct parallel meso‐slip lines prior to peak stress and persistent shear band formation, (Darve et al., 2021; Hadda et al., 2016, 2017; Rechenmacher, 2006). The orientation of the meso‐slip lines are given by the slip line solutions to the hyperbolic equations of non‐associated perfect plasticity, that is, the Coulomb angle (static solution) or the Roscoe angle (kinematic solution) (Darve et al., 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(2005) due to a lack of spatial and temporal resolution in their particle imaging velocimetry (PIV) analysis. Along these lines, in biaxial compression experiments, a number of authors have reported that pre‐peak deformation takes the form of distinct parallel meso‐slip lines prior to peak stress and persistent shear band formation, (Darve et al., 2021; Hadda et al., 2016, 2017; Rechenmacher, 2006). The orientation of the meso‐slip lines are given by the slip line solutions to the hyperbolic equations of non‐associated perfect plasticity, that is, the Coulomb angle (static solution) or the Roscoe angle (kinematic solution) (Darve et al., 2021).…”
Section: Discussionmentioning
confidence: 98%
“…In the context of accretionary wedges, Adam et al (2005) observed similar intermittent diffuse deformation preceding shear band propagation, and Dotare et al (2016) argued that this diffuse deformation was simply the sum of the activity of intermittent but thin "weak shear bands" that were not captured in the work of Adam et al (2005) due to a lack of spatial and temporal resolution in their particle imaging velocimetry (PIV) analysis. Along these lines, in biaxial compression experiments, a number of authors have reported that pre-peak deformation takes the form of distinct parallel meso-slip lines prior to peak stress and persistent shear band formation, (Darve et al, 2021;Hadda et al, 2016Hadda et al, , 2017Rechenmacher, 2006). The orientation of the meso-slip lines are given by the slip line solutions to the hyperbolic equations of non-associated perfect plasticity, that is, the Coulomb angle (static solution) or the Roscoe angle (kinematic solution) (Darve et al, 2021).…”
Section: Discussionmentioning
confidence: 99%